The only way you can dream: interfaces and intolerable spaces in Christopher Nolan's Inception. Issue 4 (3rd July 2016) - Tan, Elizabeth
Abstract: This paper examines the role of 'real space' in science fiction narratives and its implications for the relationship between humans and technology through an analysis of Christopher Nolan's feature film Inception . Drawing upon Scott Bukatman's notion of 'intolerable spaces', a term he uses to describe the imperceptible data-spaces inaugurated by the computer terminal which are made visible and accessible through science fiction and cyberpunk texts such as William Gibson's novel Neuromancer, this paper argues that Inception participates in a cultural discourse which conceptualizes the human mind through technological metaphors, conserving an idealized model of the human subject as one who can (and should) remain above, separate from, and in control of technology.